Collaborative Tourism Management Based on the Cultural Heritage and Natural Resources of the Tuo Kayu Jao Mosque in Solok Regency - Nur Syamsi Ariyani; Rini Sawitri (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study examines tourism management that integrates cultural heritage and natural resource based collaboration at Masjid Tuo Kayu Jao in Solok Regency, West Sumatra. As a historic Minangkabau heritage site, the mosque offers architectural value and natural scenery that attract visitors. Using a descriptive qualitative method through observation, interviews, and literature review, the research identifies management strategies that support sustainable tourism. Findings indicate that stakeholder collaboration is essential to balancing cultural preservation with environmental utilization. Management efforts include restoration that maintains historical integrity, the development of eco-friendly facilities, and the enhancement of community participation. This approach not only safeguards the site and its surroundings but also generates socio-economic benefits. The study contributes to the development of a collaborative tourism management model aligned with sustainability principles and the Sustainable Development Goals.